Composite resin color stability: influence of light sources and immersion media - Domingos, Patricia Aleixo dos Santos; Garcia, Patrícia Petromilli Nordi Sasso [UNESP]; Oliveira, Ana Luisa Botta Martins de [UNESP]; Palma-Dibb, Regina Guenka (Journal Of Applied Oral Science : Revista Fob, 2011)
This study evaluated the influence of light sources and immersion media on the color stability of a nanofilled composite resin. Conventional halogen, high-power-density halogen and high-power-density light-emitting diode (LED) units were used. There were 4 immersion media: coffee, tea, Coke® and artificial saliva. A total of 180 specimens (10 mm x 2 mm) were prepared, immersed in artificial saliva for 24 h at 37±1ºC, and had their initial color measured with a spectrophotometer according to the CIELab system. Then, the specimens were immersed in the 4 media during 60 days. Data from the color change and luminosity were collected and subjected to statistical analysis by the Kruskall-Wallis test (p<0.05). For immersion time, the data were subjected to two-way ANOVA test and Fisher's test (p<0.05). High-power-density LED (ΔE=1.91) promoted similar color stability of the composite resin to that of the tested halogen curing units (Jet Lite 4000 plus--ΔE=2.05; XL 3000--ΔE=2.28). Coffee (ΔE=8.40; ΔL=-5.21) showed the highest influence on color stability of the studied composite resin. There was no significant difference in color stability regardless of the light sources, and coffee was the immersion medium that promoted the highest color changes on the tested composite resin.
Keywords: Composite resins; Staining; Dental technology